Symptomatic Subjects : Bodies, Medicine, and Causation in the Literature of Late Medieval England . - Orlemanski, Julie (Alembics., 2019)
In the period just prior to medicine's modernity, England saw a remarkable upsurge in medical writing. Julie Orlemanski's Symptomatic Subjects shows how late medieval English writers drew on the discourse of medicine to narrate anew the crossings--and the conflicts--between physiology and personhood.